Quality of Asystasia leaves and stems 60 days after seeding at different shade levels. - Noordin Mokhtar, Suparjo; R. A., Halim; S., Jalaludin; C., Abu Bakar; Othman, Ahmad Shokri (1990)
The objective of this study was to determine the herbage dry matter (DM) yield and the nutritional quality of leaves and stems of Asystasia instrusa as affected by shade levels. Seedlings of the plant grown in polybags were subjected to four shade treatments : 54, 28, 14 and 7 % light in three replicates. Dry matter yield and nutritive characteristics of herbage were determined after 60 days of growth. Increasing shade levels resulted in decline DM yield (63,55,41 and 27 g m-2 respectively). Leaf nutritive quality improved with increasing shade : in-vitro digestible dry matter (IVDDM) concentration of leaves were 692, 668, 720 and 740 g kg-1 DM, respectively, while their corresponding crude protein (CP) contents were 251, 257,305 and 327 g kg-1 DM. Conversely, nutritive quality of stems decreased with shade : stem IVDDM concentrations were 766, 737, 693 and 694 g kg-1 DM while acid-detergent fiber (ADF) concentrations in stems were 283, 293, 345 and 371 g kg-1 DM. Leaf ADF and stem CO concentrations were unaffected by increased shade levels. Increasing levels of hemicellulose in leaves was accompanied by increasing IVDDM. In contrast to ADF, NDF in leaves increased with increasing shade. Phosphorus, Ca and K increased in both leaf and stem with increasing shade, while Mg decreased in leaf and remained unchange in stem. In conclusion, increased shading appears to increase leaf and decrease stem quality. This probably explain inconsistency in opinions regarding the effect of shade on quality of whole herbage.